Magneto-Elastic Stability of an Unconstrained Assembly of Coils - Alblas, J.B.; Grysa, K.W. (Engineering Transactions, 1979)
The mechanical stability of a solenoid in the form of a toroidal helix in its own magnetic field is investigated. The solenoid is mechanically unconstrained, i.e. the coils are a rigid or elastic base. In the first part of the not. supported by paper, the magnetic field, the forces and the moments acting on one single coil are calculated. The calculations are performed for the undeformed and the deformed states of the torus. The second part contains a stability analysis for the model of a circular elastic spring, which accounts for the extension and the shear deformation.